Mekanisme Angin Puting Beliung dan Dampaknya Pada Lingkungan - Radita Nur Nilam Sari; Sudarti (Universitas Nusa Putra, 2025)
Tornadoes or usually called tornadoes are a natural phenomenon that causes very significant damage to buildings, nature and infrastructure, and has a serious impact on people's lives. Studying the mechanisms by which tornadoes or tornadoes occur and their impact on the environment is important as an effective natural disaster preparedness and mitigation effort. This research uses a literature review method by collecting 25 relevant journals as review material. Tornadoes can cause serious damage to buildings, nature and infrastructure, and also have the potential to cause harm to local communities. A better understanding of tornado mechanisms and their environmental impacts is critical for the development of effective risk mitigation strategies and better spatial planning in tornado-prone areas. This study contributes valuable insights into tornado mechanisms and their environmental impacts that serve as a basis for the development of effective mitigation measures and improved protection efforts against future tornado hazards.